KLASIFIKASI PENGADUAN PENGGUNA SUBSIDI BBM MENGGUNAKAN ALGORITMA NAÃVE BAYES - Sainunu Boy; Yuni; Asri Yadi (P3M STMIK Profesional Makassar, 2023)
Fuel subsidy program is one of the government programs aimed at helping people meet their daily transportation needs. However, there are still many obstacles faced by fuel subsidy users such as limited quota and lack of information about the program mechanism. Therefore, this study was conducted to predict the constraints faced by fuel subsidy users using NaÃ¯ve Bayes algorithm. This study involved 100 respondents spread across Jabodetabek area and conducted an online survey as a data source. The result of data analysis showed that classification model using NaÃ¯ve Bayes algorithm was quite good in predicting the constraints faced by fuel subsidy users with an average accuracy value of 0.82.Based on these results, it can be concluded that the fuel subsidy program still has several obstacles in its implementation so efforts need to be made to improve the effectiveness and efficiency of the program for more benefits to all levels of society.